2008
DOI: 10.1074/jbc.m802445200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Modules of RNA Polymerase Required for Transcription from Promoters Containing Downstream Basal Promoter Element GGGA

Abstract: We recently described a novel basal bacterial promoter element that is located downstream of the ؊10 consensus promoter element and is recognized by region 1.2 of the subunit of RNA polymerase (RNAP). In the case of Thermus aquaticus RNAP, this element has a consensus sequence GGGA and allows transcription initiation in the absence of the ؊35 element. In contrast, the Escherichia coli RNAP is unable to initiate transcription from GGGA-containing promoters that lack the ؊35 element. In the present study, we dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…Consistent with a previous report (10), our data indicate that Taq RNAP is not compromised in terms of its intrinsic affinity to the single-stranded non-template segment of transcription bubble bearing the −10 element. However, in agreement with the known biochemical results (32), we found that the dependence of RNAP affinity on the sequence of discriminator is different in Taq and E. coli RNAPs: the ratio of affinities of oligos 3 and 4 bearing, respectively, the GGGA and CCCT discriminator sequences is 150 for Taq Eσ A and only 7 for to Ec Eσ 70 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with a previous report (10), our data indicate that Taq RNAP is not compromised in terms of its intrinsic affinity to the single-stranded non-template segment of transcription bubble bearing the −10 element. However, in agreement with the known biochemical results (32), we found that the dependence of RNAP affinity on the sequence of discriminator is different in Taq and E. coli RNAPs: the ratio of affinities of oligos 3 and 4 bearing, respectively, the GGGA and CCCT discriminator sequences is 150 for Taq Eσ A and only 7 for to Ec Eσ 70 .…”
Section: Discussionsupporting
confidence: 92%
“…The substitutions caused considerable, ∼100-fold, change in affinity to Taq Eσ A , whereas only ∼10-fold change was observed with Ec Eσ 70 (Figure 4A, Table 1). These data correlate well with reported effects caused by similar sequence changes on efficiencies of transcription initiation by these enzymes, suggesting that the downstream promoter motif is more important for Taq RNAP than for E. coli RNAP (32). …”
Section: Resultssupporting
confidence: 86%
“…Taq RNAP mutants with deletions of the β flap tip and αCTDs are unable to efficiently recognize −10/−35 promoters (24). Thus, to test termination by these RNAP mutants we used a DNA template that contained an extended −10 promoter, gal P1, fused to the tR2 terminator.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, nonconserved substitutions in region 1.2 in Taq A may affect the open complex stability through weakening the -DNA contacts. Importantly, however, in contrast to the previously studied alanine substitutions in 70 , A -specific substitutions do not disrupt interactions of region 1.2 with DNA, because A region 1.2 was shown to specifically recognize the GGGA element downstream of the Ϫ10 element in promoter complexes of Taq RNAP (10,18).…”
Section: Discussionmentioning
confidence: 83%
“…1A), incompatible with double-stranded DNA conformation, explaining previously established roles of region 2 in promoter recognition, DNA melting, and stabilization of RNAP-DNA interactions (1,(13)(14)(15)(16)(17). Although the exact position of the nontemplate DNA strand downstream of the Ϫ10 element remains unknown, structural modeling, site-specific cross-linking, and biochemical analyses suggest that this DNA segment may directly contact region 1.2, depending on the DNA sequence context (10,11,18,19). Amino acid substitutions at various positions of region 1.2 in Eco 70 were shown to decrease RNAP activity, inhibit promoter DNA melting, and destabilize the open promoter complex (Fig.…”
mentioning
confidence: 96%